Temporal lob epilepside lateralize edici bulgu olarak materyal spesifik bellek bozukluğu - Hanoğlu, Lütfü; Şengül, Hakan Serdar; Erbayat, Ebru; Özmansur, Elif Nurdan; Keskinkılıç, Cahit; Demirci, Sema; Polat, Burcu; Yılmaz, Nesrin; Uzan, Mustafa; Özkara, Çiğdem (Kare Publishing, 2014)
Amaç: Belleğin materyal spesifik özelliği ile verbal bellek sol, nonverbal bellek de sağ temporal bölge ile ilişkilendirilir. Bu çalışmada hastaların bireysel olarak cerrahi öncesi dönemde verbal ve nonverbal bellek işlevleri incelenmiştir. Gereç ve Yöntem: İstanbul Üniversitesi Cerrahpaşa Tıp Fakültesi’nde temporal lob epilepsisi (TLE) tanısı almış ve cerrahi tedaviye hazırlanmış toplam 137 hastada, (70 erkek ve 67 kadın) verbal ve nonverbal bellek testlerinin sonuçları nöbetlerin başladığı taraf (sağ, n=73, sol, n=56 veya iki taraflı n=8) ile olan ilişkileri bakımından incelenmiştir. Verbal bellek için sözel bellek süreçleri testi (SBST) ve nonverbal bellek işlevleri için Wechsler Memory Scale görsel alt test (WMS/G) testleri uygulanmıştır. Bulgular: Sol TLE’li hastaların %44.6’sı, sağ TLE’li hastaların ise %5.5’i materyal spesifik bellek bozukluğu göstermiştir. Hastaların büyük çoğunluğunda hem verbal, hem de nonverbal bellek testleri normal sınırlar içerisinde izlenmiştir (sol TLE %28.6/sağ TLE %50.7). Ayrıca hem verbal, hem de nonverbal belleğin etkilendiği, “global” bir etkilenme de oldukça sık izlenmiştir (sol TLE %21.4/sağ TLE %17.8). Sol TLE’li hastalarda sağ temporal loba atfedilen nonverbal bellekte düşük performans gösteren hasta sayısı az (%5.4) iken sağ TLE’li hastalarda bu oran oldukça yüksektir (%26). Sonuç: Bireysel değerlendirmede sağ TLE’li hastalarda karşı tarafa ait materyal spesifik bellekte düşük performans izlenmesi materyal spesifite teorisinin gözden geçirilmesini gerektirir.

Objectives: Verbal memory is associated with left and non-verbal memory is associated with right temporal lobe because of the material specificity of the memory. In this study, it is examined verbal and nonverbal memory functions by individual assessment of the patients during presurgical period. Methods: Total of 137 patients (70 men and 67 women) who were diagnosed for TLE and prepared for surgical treatment at Istanbul University Cerrahpasa School of Medicine were assessed for the association of verbal and nonverbal test results and the side of the seizure origin (right n=73 left, n=56 or bilateral n=8). Verbal memory processing scale (SBST) for verbal memory and Wechler Memory Scale Visual Subtest (WMS/G) for non-verbal memory functions were applied to the patients. Results: 44.6% of patients with left TLE but 5.5% of right TLE showed material specific memory impairment. Both verbal and nonverbal memory tests were seen in normal limits in the majority of the patients (left TLE 28.6%, right TLE 50.7%). Besides, `global` effect in which verbal and also nonverbal memory were affected was seen quite frequently (left TLE 21.4%, right TLE 17.8%). While the number of the patients with left TLE who showed incompatible low performance on nonverbal memory was low (5.4%), this rate was found to be quite high in patients with right TLE (26%). Conclusion: In individual evaluation, observation of low performance on material specific memory of contralateral side in patients with right TLE requires overview.
Material specific memory impairment as a lateralizing finding in temporal lobe epilepsy
Keywords: Bellek; Cerrahi; Materyal Spesifite; Nöropsikoloji; Prognoz; Temporal Lob Epilepsi; Memory; Surgery; Material Specifity; Neuropsychology; Prognosis; Temporal Lobe Epilepsy